First lactation production and reproduction performance of Phule Triveni cattle in hot arid region of Maharashtra - AMBHORE, G S; SINGH, AVTAR; DEOKAR, D K; GUPTA, A K; SINGH, MANVENDRA; PRAKASH, VED (The Indian Journal of Animal Sciences, 2017)
The present investigation was carried out to study the effects of genetic and non-genetic factors on first lactation production and reproduction traits of 493 Phule Triveni cattle sired by 55 bulls during 1976-2012 maintained at Research-Cum Development Project on Cattle, Mahatma Phule Krishi Vidyapeeth Rahuri, District Ahmadnagar, Maharashtra, India. The average FLTMY was 2855.40±42.67 kg with an average FLL 331.03±3.01 days and the FL300DMY was found to be 2646.77±39.30 kg. The average AFC, FCI, FSP and FDP was 985.41±1.93, 430.32±4.01, 151.07±5.10 and 93.45±2.84 days, respectively. The effect of season of calving was found to be non-significant on all production and reproduction traits except FL300DMY which was affected significantly. However, the effect of period of calving was found to be highly significant on all production and reproduction traits except FSP on which effect was found to be significant. The effect of the sire was found to be significant on FL300DMY, FDP and AFC. The heritability (h2) estimates for production and reproduction traits were found to be moderate to high. The highly significant genetic and phenotypic correlation was found between production and reproduction traits. The present investigation revealed that FLTMY, FL300DMY and AFC could be improved through selection and can be used for further improvement programmes.